Data for pressure ulcers and skin infections after cochlear implantation - Hui-Shan Hsieh; Chee-Yee Lee; Hung-Pin Wu; Ming-Ying Zhuo; Chung-Feng Hwang (Data in Brief, 2020)
This article contains data concerning the research article entitled “Pressure ulcers and skin infections after cochlear implantation: A delayed yet serious issue” (Hui-Shan Hsieh, Chee-Yee Lee, Hung-Pin Wu, Ming-Ying Zhuo, and Chung-Feng Hwang) [1]. This data article reports the causes of skin flap pressure ulcer over the antenna site and protocol for the clinical managements. The patients with cochlear implant (n = 315) were enrolled. We used the National Pressure Ulcer Advisory Panel (NPUAP) pressure injury staging system to grade injury severity in all patients. The data included in this article are as follows: the clinical characteristics of patients, baselines variables between groups with and without pressure ulcer, the severity of skin flap reactions based on the NPUAP pressure injury system and corresponding interventions, related clinical details of patients with pressure ulcer, This article will be valuable for routine clinical practice as serving as a paradigm.